Use of supervised exercise during recovery following sports-related concussion - Popovich, M.; Almeida, A.; Freeman, J.; Eckner, J. T.; Alsalaheen, B.; Lorincz, M.; Sas, A. (Clinical Journal of Sport Medicine, 2021)
Objective: To assess the safety of supervised exercise (SE) in acute sport-related concussion (SRC) and its influence on recovery.